2011
DOI: 10.3892/mmr.2011.647
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral zone of the prostate is more prone to tumor development than the transitional zone: Is the ETS family the key?

Abstract: Abstract. Predisposition to develop prostate cancer (PCA) varies among the prostate zones, with the peripheral zone (PZ) more prone to tumor development than the transitional zone (TZ). In view of the fact that molecular differences between the zones may explain this difference, combined with the findings that translocations between TMPRSS2 and several ETS members are frequently observed in PCA, we hypothesized that the ETS family may be crucial to explaining this difference. Normal tissues from the PZ and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In our study, we used tissues from prostates of patients undergoing radical prostatectomy for prostate cancer. Most prostate cancers are located in the peripheral zone (49,54). Our samples were exclusively taken from the periurethral zone, which is usually not affected by prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used tissues from prostates of patients undergoing radical prostatectomy for prostate cancer. Most prostate cancers are located in the peripheral zone (49,54). Our samples were exclusively taken from the periurethral zone, which is usually not affected by prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken immediately after prostatectomy, following macroscopical examination by a uropathologist. All tissues were taken from the periurethral zone, considering that most prostate cancers arise in the peripheral zone (49,54). Upon pathologic evaluation, only tissue samples that did not exhibit histological signs of neoplasia, cancer, or inflammation were collected.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Shaikhibrahim et al . reported that ERG and ETV1 are up-regulated in the glands of the peripheral zone comparing with the transitional zone of the prostate, and that PEA3 rearrangements can occur de novo in metastatic lesions of rearrangement-negative primary tumors (contrarily to ERG rearrangements) [ 30 , 53 ]. Searching for additional validation, we used data from GSE26242 to look for differentially expressed genes using the interactive web tool GEO2R from the National Center for Bioinformatics (NCBI) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Informed written consent was obtained from the participants; data were analysed anonymously. Tissues were taken from the periurethral zone, while most prostate tumors are located to the peripheral zone [ 31 , 32 ]. Tissue samples did not exhibit histological signs of neoplasia, cancer, or inflammation.…”
Section: Methodsmentioning
confidence: 99%